الإدارة الاستراتيجية على وفق أخلاقيات المهنة والمنظمة - الجنابي، محمد حسين على حسين (مركز رفاد للدراسات والأبحاث, 2020)
إن الواقع الاجتماعي لأخلاقيات الأعمال وهيمنتها المتزايدة على كافة الجوانب الفكرية والتطبيقية في سلوك الفرد والمنظمة والمجتمع يؤثر وبسرعة على الواقع الحالي ومستقبل منظمات الأعمال، وانطلاقا من أهمية الأخلاق وقيادتها للفرد والمجتمع وصيرورتها هويته المميزة في محافل التقييم والاعتبار المعرفي والعملي فإن الحاجة إلى تحديد مستوى العلاقة والتأثير وشدة كل منهما في توجيه وتغيير ملامح منظمية متعددة منها الإدارة الاستراتيجية التي تعبر عن التوجهات المستقبلية عبر رؤية ورسالة وأهداف محددة وصياغة استراتيجية كفؤة وتحقيق كل ذلك بعد تحليل دقيق لواقع الأبعاد البيئية الداخلية والخارجية، ليقدم حصيلة تراكم فلسفي مميز ووفقا لمنظور ومدخل أخلاقي يحدد قبول أو رفض كمي أو نوعي لتلك الأبعاد. يعزز هذا البحث أفكاره بحالة تطبيقية لإغناء المفاهيم الفكرية للمتغيرات المبحوثة تبعا لآراء عينة من المديرين وقيادات منظمية اختيرت بعناية في المصرف الدولي الإسلامي (شركة خاصة) لكشف ملامح فكرية سليمة تبقى منظمات الأعمال بأشد الحاجة لتحديدها والتميز بها في موقع وموقف استراتيجي يحقق أهدافها وأهداف أصحاب المصلحة على اختلاف نواياهم وطلباتهم. فضلا عن حالات النمو والتنافس الذي يلازم الفكر الاستراتيجي المتجدد وفاعلية ممارسات قيادية وسلوك ريادي واعد. وينهي البحث مساره العلمي بمجموعة من الاستنتاجات أبرزها التغلغل الأخلاقي الفاعل والمعبر عن توأمة الأخلاق واستراتيجية المنظمة معا وفي كل حين، فضلا عن التوصيات التي تؤكد فاعلية الاستراتيجية عندما تلازم أخلاق سامية مميزة يفخر الجميع بحملها داخل وخارج المنظمة.
The social reality of business ethics and its increasing domination of all aspects of intellectual and applied behavior of individual, organization and society effects on current reality and future of business organizations, and based the importance of ethics and leadership of the individual and society, then become distinctive identity in forums evaluation and knowledge, practical consideration, that needs to determine the level of relationship and effect in strategic management, which reflects the future directions through a vision, mission and main objectives with a good strategic formulate, implementation, analyzing the internal and external environmental, then provides the outcome of a distinctive philosophical and perspective of ethical approach to determines the acceptance or rejection of quantitative or qualitative dimensions. This research reinforces his ideas by applied case to enrich the intellectual concepts of the variables researched according to the opinions of a sample of managers and organizational leaders carefully selected in the International Islamic Bank (private company) to uncover sound intellectual features remain business organizations most need to identify and distinguish them in a strategic position and achieve its objectives and the objectives of stakeholders Different intentions and requests. As well as the cases of growth and competition that accompany renewed strategic thought and the effectiveness of leadership practices and leadership behavior promising. The research concludes its scientific process with a set of conclusions, most notably the effective ethical penetration as a twinning of ethics with strategy of the organization together for all times, so recommendation that is confirm the effectiveness of the strategy when inherent high moral ethics proud to carry them inside and outside the organization.
Keywords: أخلاقيات الأعمال -- الأخلاق المهنية -- إستراتيجية المنظمة -- الإدارة الإستراتيجية